2003
DOI: 10.1021/ic026085h
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Motions in the Solid State:  the Thermochromic Nitro−Nitrito Interconversion in Nickel(II) Bis(diamine) Complexes

Abstract: The NO(2)(-) ion, in the trans-octahedral [Ni(II)(N,N'-dimethylethylenediamine)(2)(NO(2))(2)](H(2)O) complex, coordinates the metal through the nitrogen atom (nitro form). On heating the solid complex, the anion rotates to give nitrito coordination (oxygen bound), according to a reversible process. The coordination mode of NO(2)(-) to Ni(II) is related to the steric interplay between the anion and the alkyl substituents on the diamine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…220 °C ( 1′ and 2′ , respectively), we could not draw a clear conclusion about their structural transformations. However, on the basis of the UV studies and reported works, it is expected that the structural transformation accompanied by a reversible color change can be accounted for by the liberation and recoordination of two water molecules. , Removal of the coordinated water molecules generates desolvated purple crystals of 1 and green crystals of 2 by changing the coordination geometry of Co­(II) and Ni­(II), respectively, , from octahedral to square-planar (Figure ), which can revert back to the octahedral geometry upon exposure to water.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…220 °C ( 1′ and 2′ , respectively), we could not draw a clear conclusion about their structural transformations. However, on the basis of the UV studies and reported works, it is expected that the structural transformation accompanied by a reversible color change can be accounted for by the liberation and recoordination of two water molecules. , Removal of the coordinated water molecules generates desolvated purple crystals of 1 and green crystals of 2 by changing the coordination geometry of Co­(II) and Ni­(II), respectively, , from octahedral to square-planar (Figure ), which can revert back to the octahedral geometry upon exposure to water.…”
Section: Resultsmentioning
confidence: 99%
“…There are also numerous reports on Ni­(II) complexes that illustrate a reversible thermochromic behavior, but the majority of these complexes are mononuclear in nature. Contrarily, reports on Ni­(II)-based CPs with a reversible thermochromic behavior are extremely rare …”
Section: Introductionmentioning
confidence: 99%
“…These findings also indicate that 160 K should be the optimal temperature for further photo-crystallographic experiments. Through the analysis of similar literature examples (Chattopadhyay et al, 2005;Chao et al, 2012;Das et al, 1998;Hortalá et al, 2003;Laskar et al, 2000;Ribas et al, 1984;Hitchman & Rowbottom, 1982) supported by the isolated-molecule computations of harmonic normalmode frequencies conducted for the molecule (see the supporting information), it was possible to identify and assign two of these bands (note the computed values tend to be overestimated). It appears that the 556 cm À1 band can be assigned to a wagging mode, !…”
Section: Figurementioning
confidence: 86%
“…Ni­(II) ion is one of the 3d transition metals that have a variety of coordination numbers and geometries, each with its own visible color. , Consequently, it is suitable to use a Ni­(II) center for fabrication of a new multistimuli responsive chromic CP. Vapochromism of some Ni­(II) complexes has been reported. ,, For instance, Baho and colleagues showed that the addition of CH 3 CN vapor can cause a change in coordination modes of nitrate ligands, leading to a shift in d–d bands of a Ni­(II) complex and a change in its color .…”
Section: Introductionmentioning
confidence: 99%
“…Vapochromism of some Ni­(II) complexes has been reported. ,, For instance, Baho and colleagues showed that the addition of CH 3 CN vapor can cause a change in coordination modes of nitrate ligands, leading to a shift in d–d bands of a Ni­(II) complex and a change in its color . In case of thermochromism, it has been extensively observed in many Ni­(II) systems. Heat frequently induces the loss of lattice and coordinated solvent molecules, resulting in a structural transformation accompanying with the change in coordination environment. , Until now, there are many reports on mechanochromic behavior in coordination compounds. The reported mechanochromism generally occurs with a change in luminescent signal because most of them are constructed from 5d elements, such as Pt­(II) and Au­(I) ions, as well as some 3d 10 elements, such as Cu­(I) and Zn­(II) ions. ,, The mechanical force can alter metallophilic interactions between metal centers, resulting in the luminescent color change.…”
Section: Introductionmentioning
confidence: 99%